Sunni school of thought in Southeast Asia: Muslim intellectual responses to new ideological trends = Fahaman Ahlussunnah wa al Jama’ah di Asia Tenggara: pemahaman dan tanggapan golongan cerdik pandai muslim terhadap ideologi-ideologi baharu - Wahyono, Zubaidi; Gamon, Alizaman Dumangcag (International Islamic University Malaysia, 2020)
The study explores various definition of Ahl al-sunnah wa al-jamÉ‘ah and its main principles as understood by Muslim scholars in Southeast Asia as well as the con-troversies that had taken place over the years. The study highlights the responses of Muslim scholars and religious authorities in resolving the controversies within the Muslim communities. The controversies started when the authority of the Sunni school of thought in ASEAN Muslim communities had been tested with the emergence of the rationalist Muslim group and Salafism as advocated by Wahabism. On the other hand, the influence of Shi'ism and other foreign ideologies such as pluralism and liberalism had augmented the complexity of the issue. The study employed qualitative research methodology studying both the literature and the observations to ensure the validity of the source. Given the scarcity of literature written by Muslim scholars, this study relies on primary sources such as unpublished works, interviews, and fieldwork in addition to library research. Among the important findings of the study is that there are various interpretations of Ahl al-Sunnah wa al jamÉ‘ah due to various methods adopted in interpreting the theological stance of Islam. These differences somehow had caused the Muslims in the region and their scholars divided and disunited. The new ideologies and philosophies had contributed to the complexity of the issue and challenged the Muslim scholars to come up with an uninformed opinion to solve the problems. It is therefore recommended in this study that a unified system of thought is crucial to at-taining the socio-religious agenda of ASEAN Muslim communities.